Effect of prostaglandin F2alpha, oxytocin and butylated hydroxytoluene on enzyme activities of crossbred (HF x Hariana) bull semen - ARANGASAMY, A; SINGH, L P; ANSARI, M R; GUPTA, O P; BISHT, G S (The Indian Journal of Animal Reproduction, 2003)
Semen samples were collected from two crossbred bulls (HF x Hariana) and diluted in tris withthree combinations of additives i.e., prostaglandin Fp, oxytocin and butylated hydroxytoluene (2mM/ml) and frozen in liquid nitrogen. The enzyme activities (GOT, GPT, ACP and AKP) were evaluatedat prefreeze and postfreeze stage. Except GPT the other enzymes showed no significant differencebetween treated and control groups at prefreeze stage. The value of GOT and GPT differed significantlybetween treatment and control groups, whereas, there was no significant difference in ACP and AKPat postfreeze stage. The enzymatic activity in the post-thaw semen treated with these additives revealeda lower leakage of enzyme than control.
Keywords: Bull; semen; transaminases; phosphatase; PGF2alpha; oxytocin; BHT